Evaluation of some physical, chemical and sensorial parameter of turkish coffee trade in the Albanian market - Shehaj, Alketa; Morina, Ariola (Journal of Biological Studies, 2022)
Coffee is a product that is used all over the world because it has a lot of effects on the human body. There are different types of coffee in the market but in the Albanian market, Turkish coffee distinguishes from other types because it is traditional, and is used mainly by housewives. The extraction method is boiling, where mostly all the soluble substances are passed into the cup. We have collected some samples of Turkish coffee that is in trade in the Albanian market and have evaluated their physical, chemical and sensorial properties. All the Turkish coffee samples are processed in the Albanian region, where are situated some good factories with modern technology. The study aims to evaluate the quality of Turkish coffee that is produced in the Albanian market and for this; we have determined some physical and chemical properties such as humidity, ash, coffee oil, protein, acidity and fibres. We also evaluated the sensorial properties and made a correlation between acidity and sensorial properties. All the data taken for the grinded Turkish coffee have shown that the level of humidity ranged from 1.6 to 3.5%. The ash from 4.01-4.68 %, acidity from 0.7-0.95%, protein from 14-16.7%, carbohydrates from 44.5-69.56%, coffee oil from 13.8-15.76% and fibers from 31.85-34.56%. A correlation was found between the level of acidity and the diagram of sensorial properties.